2006
DOI: 10.1083/jcb.200511124
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesions are hotspots for keratin filament precursor formation

Abstract: Recent studies showed that keratin filament (KF) formation originates primarily from sites close to the actin-rich cell cortex. To further characterize these sites, we performed multicolor fluorescence imaging of living cells and found drastically increased KF assembly in regions of elevated actin turnover, i.e., in lamellipodia. Abundant KF precursors (KFPs) appeared within these areas at the distal tips of actin stress fibers, moving alongside the stress fibers until their integration into the peripheral KF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 28 publications
(50 reference statements)
8
102
0
1
Order By: Relevance
“…1C, arrowhead), and may be related to the presence of hemidesmosomes [40]. Alternatively, it has been shown that focal adhesions may act polymerizing keratin IFs [41]. It is difficult to conceive how this mechanism may be related to the bulk of the apical IFs, but it may be related to the small basal population of IFs.…”
Section: Location Location Location: Apical Distribution Of Intermementioning
confidence: 98%
“…1C, arrowhead), and may be related to the presence of hemidesmosomes [40]. Alternatively, it has been shown that focal adhesions may act polymerizing keratin IFs [41]. It is difficult to conceive how this mechanism may be related to the bulk of the apical IFs, but it may be related to the small basal population of IFs.…”
Section: Location Location Location: Apical Distribution Of Intermementioning
confidence: 98%
“…1 and Fig. 5B; supplementary material Movies 1, 2, 8) ( Windoffer et al, 2006;Yoon et al, 2001). Cells with increased KF-network reorganization, such as migrating cells, show a considerable increase in KFP formation ( Fig.…”
Section: Nucleationmentioning
confidence: 99%
“…1) (Windoffer et al, 2006;Woll et al, 2005). Focal adhesions are important regulators of keratin nucleation (Windoffer et al, 2006) by direct and/or indirect molecular association [ (Steinbock et al, 2000); for other IFs, see the following references (Kreis et al, 2005;Nikolic et al, 1996;Spurny et al, 2008;Steinbock et al, 2000;Sun et al, 2008a;Sun et al, 2008b;Tsuruta and Jones, 2003)] and/or by signalling (e.g. Omary et al, 1998;Woll et al, 2007).…”
Section: Nucleationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is precedence for FAs being important for IF organization (Bhattacharya et al, 2009;Burgstaller et al, 2010;Windoffer et al, 2006). Thus, we next determined if the plectincontaining cFAs influence the distribution of the IF keratin cytoskeleton of rAEC (Eisenberg et al, 2011;Takawira et al, 2011).…”
Section: Fa Double Ring Formation Is Plectin Dependentmentioning
confidence: 99%